Vibrating things make sound - King, Virginia; Mancini, Rob (Nelson South Melbourne, 1994)
Vibrating Things Make Sound" is an engaging children's book that introduces young readers to the concept of sound through vibration. The book explains how sound is produced when objects vibrate, whether it$1 (Bs a musical instrument, a person's voice, or everyday items.s